Pengabdian Kepada Masyarakat Melalui Workshop Peningkatan Pemahaman Guru Mengenai Pembelajaran Berbasis STEAM - Rahma Nasir; Ucok Manigor Jokkas Siahaan; Manto Lumban Gaol; Ni Made Intan Kertiani; Churun Lu’lu’il Maknun (Pendidikan Matematika, FKIP Universitas Mataram, 2022)
The purpose of this community service is to improve teachers' understanding of STEAM learning. The problem faced by teachers is the lack of information on how to choose the context of STEAM learning, lack of event of sharing session with teachers who have implemented STEAM to teachers who want to carry out innovative learning. Teachers need training on STEAM based on the evaluation form that has been shared by the team before the STEAM workshop is held. It aims to identify problems, determine problem solutions, and determine the timing of activities. The stage of implementation of activities is carried out in the form of a model of lectures, discussions, and assignments. The material provided includes the definition of STEAM, STEAM social context and followed by sharing sessions by teachers who have implemented STEAM learning in schools. The result of this community service is that teachers can design learning evidenced by STEAM-based learning design tasks that have been collected by 24 teachers in google classroom. Participants' response to the implementation of activities is very good, participants hope that this kind of activity can be re-organized for the future.